2000
DOI: 10.1034/j.1600-0714.2000.290101.x
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblasts and matrix components in healing palatal wounds in the rat

Abstract: In order to identify wound contraction and scar formation during palatal mucoperiosteal wound healing in growing rats, the temporal and spatial distribution of myofibroblasts and matrix components were determined immunohistochemically. Myofibroblasts were found in the mucosal part of the palatal wound tissue between 4 and 22 days, with the highest density at 8 days post-wounding. The number of collagen type I and type III fibers gradually increased until about 8 days postwounding, and thereafter the staining i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 20 publications
1
18
0
2
Order By: Relevance
“…In agreement with our results Cornelissen et al, found that normally no alpha SMA was found until 4 days post wounding and the number of positive cells increase from 4 to 8 days post wounding, at 8 or 9 days the majority of the granulation tissue fibroblasts were stained for α SMA and at about 12 days the proportion of α -SMA positive cells are steadily decreased till 22 post wounding where they found no single positive myofibroblast in the newly formed connective tissue (33) .…”
Section: Discussion:-supporting
confidence: 81%
“…In agreement with our results Cornelissen et al, found that normally no alpha SMA was found until 4 days post wounding and the number of positive cells increase from 4 to 8 days post wounding, at 8 or 9 days the majority of the granulation tissue fibroblasts were stained for α SMA and at about 12 days the proportion of α -SMA positive cells are steadily decreased till 22 post wounding where they found no single positive myofibroblast in the newly formed connective tissue (33) .…”
Section: Discussion:-supporting
confidence: 81%
“…In palatal scar tissue in rats, collagen bundles mainly have a parallel and transversal orientation. 33,34 Because the fibrils in our scaffolds are oriented randomly, this may finally result in a more random pattern of newly formed collagen.…”
Section: Discussionmentioning
confidence: 98%
“…48,49 In palatal wounds of rats, myofibroblasts are mainly present between 4 and 22 days, with a peak intensity after 1 week. 33 On purely morphologic grounds, Dabelsteen and Kremenak 50 described the presence of myofibroblasts in open palatal wounds in dogs between 1 and 2 weeks. Also, in skin wounds, myofibroblasts are abundantly present up to 2 weeks after wounding.…”
Section: Discussionmentioning
confidence: 99%
“…The intervals used to evaluate angiogenesis and the formation of myofibroblasts were 7 and 21 days after the surgical procedure. Myofibroblasts are found in the scar tissue between the fourth and sixth day after injury, with greater proliferation between 8 and 30 day 8 of the healing process 9 .…”
Section: Discussionmentioning
confidence: 98%